Securing the Right to Housing: Legal Review of Rusunawa on Local Government Land in Brebes - Pebriyani, Aulia (Indonesian Journal of Agrarian Law, 2025)
The development of low-cost rental apartments (Rusunawa) is a government initiative aimed at providing decent housing for low-income communities (MBR), especially in areas with high urbanization rates such as Brebes Regency. However, the utilization of regional government-owned land for the construction of Rusunawa raises legal issues regarding ownership status and residents' housing rights. This study aims to examine the legal provisions surrounding the use of state/regional land for apartment development, as well as the form of ownership or housing rights granted to residents of public apartments built on such land. The research adopts a normative legal method with a descriptive-analytical approach, using primary data from statutory regulations and secondary data from field observations at the Brebes Rusunawa. The findings reveal that the land remains the property of the regional government and cannot be transferred to residents. Thus, residents are granted only temporary rental rights through agreements with the local government. These rights are non-permanent, non-inheritable, and non-transferable—unlike the Ownership Certificate of Strata Title Units (SHMSRS). Accordingly, legal regulations in Brebes affirm that housing rights in Rusunawa are temporary and based solely on lease agreements, in accordance with the Regent Regulation and Government Regulation on the Management of Regional Assets.